Fatores associados à perda do excesso de peso em obesos mórbidos submetidos ao by-pass gástrico em “y de roux” ao longo de sessenta meses - Barhouch, Anália Santiago (2015)
Introduction: The objective of this study was to analyze the factors associated with variability of body mass index (BMI) and percentage of excess weight loss (%EWL) of patients undergoing Roux-en-Y gastric by-pass (RYGB) throughout 60 months. The following factors were analyzed: gender, age, surgical access (laparotomy vs. laparoscopy), preoperative BMI, waist circumference (WC), type 2 diabetes mellitus (T2DM), high blood pressure, and dyslipidemia.Material and Methods: Retrospective cohort study using a convenience sample of 2,070 patients of both gender, aged 18 to 65 years, undergoing RYGB between 2000 and 2013. Patients were divided into quartiles according to the distribution of minimum BMI and maximum %EWL. Follow-up lasted 60 months. Results: The four most significant factors in terms of variation of BMI over 60 months in descending order were preoperative BMI, preoperative WC, surgical access, and age. Regarding %EWL, the most important factors were surgical access, preoperative BMI, preoperative WC, and age (p<0.001). After 36, 48, and 60 months, approximately 50% of patients had BMI>30 kg/m². As for %EWL, we found that 17% of patients had %EWL <50% and 40 % of patients had between 50% to 75% %EWL and 24 % of patients had %EWL above 75% to 90% and 19% of patients had %EWL above 90%. Conclusion: There was a more significant decrease in BMI and %EWL in the first 6 months, followed by a gradual increase in both outcomes. Considering the association with BMI and %EWL, the most important factors were: pre-operatory BMI and waist circumference, surgical approach and age. Further studies are needed to better understand the role of these factors, including their role as possible event predictors.